INFLUENCE OF DEEP MARGIN ELEVATION ON STRESSES AND DEFORMATIONS OF CLASS II CAVITY MOLARS: A THREE-DIMENSIONAL FINITE ELEMENTS ANALYSIS (CIPEEX, 2023)
The restoration of teeth with large cavities is common and represents a challenge in dentistry, especially those that present deep proximal cavities. The Deep Margin Elevation (DME) technique is a method used to restore teeth with subgingival proximal cavities and to relocate the subgingival cervical margins to an equigingival or supragingival position. In this study, the influence of deep margin elevation on proximal boxes of mesio-occluso-distal (MOD) cavities was evaluated using the Finite Element Method (FEM), in comparison with clinical crown lengthening in the biomechanics of lower molars. The study conducted was a laboratory-based computational simulation. Three models were obtained: H-Healthy Tooth; EMP-Deep Margin Elevation; AC-Clinical Crown Lengthening. The response variables were: maximum principal stress, von Mises stress, and maximum principal displacement for all the involved structures. The 3D reconstruction of tomographic images of a lower first molar was carried out with the help of the InVesalius software, exported to the SolidWorks CAD software; to the Ansys Workbench software, and the analysis was performed using FEM. Axial loading was applied at 3 contact points on the occlusal surface, simulating tripod contact between arches in the mandibular intercuspation position with a magnitude of 400N. For the enamel of model H, the highest stress values were observed, followed by the EMP and AC models. In the Deep Margin Elevation model, the values were similar to those found in the healthy tooth. The increase in clinical crown led to higher stress values for the bone tissue, dentin, and inlay restoration.
Keywords: Deep Margin Elevation; Class II Restoration; Three-Dimensional Finite Elements; Inlay